Modelamiento estático de una roca reservorio de la formación Carbonera, de la parte oeste de la cuenca de los llanos Orientales, departamento del Casanare (2023)
Geological modeling in a prospective zone for hydrocarbon production allows companies increase well drilling efficiency by considering factors such as initial pressure, porosity, permeability, water saturation and volume of shale, among others. For To carry out this study, the Petrel software was used, which facilitated the geophysical interpretation, correlating well data, creating height maps to identify areas of interest, as well as petrophysical and facies modeling. Additionally, Geographics software was used to determine water saturations, porosity, effective porosity and shale volume. From These analyses, it was possible to identify a prospective area for drilling an exploratory well, taking into account the local geology of the area.